Natural Science and Technology Terminology in the Sesotho sa Leboa Monolingual Dictionary - Mojapelo, W.M.; Mojela, V.M. (Lexikos, 2009)
Abstract: The main purpose of this article is to make a comparative analysis of the structural and the lexical differences between coinage and transliteration, as methods for the acquisition of foreign natural sci-ence and technology lexical items, which are meant for inclusion in the Sesotho sa Leboa comprehensive monolingual dictionary, PukuntÅ¡utlhaloÅ¡i ya Sesotho sa Leboa. With the exception of the multilingual glossaries ('dictionaries' as they are called), which are compiled by the National Language Service of the Department of Arts and Culture, the Sesotho sa Leboa National Lexicography Unit does not at present have any monolin-gual dictionary specializing in specific subjects like natural science and technology. As a start, the Lexicogra-phy Unit decided to include this specialized terminology in the second edition of its comprehensive monolin-gual dictionary. The main purpose for lemmatizing the natural science and technology terminology is to give these lexical items comprehensive definitions in Sesotho sa Leboa, instead of 'a one word translation defini-tion' as is the case in the bilingual and multilingual dictionaries.Keywords: TRANSLITERATION, COINAGE, COINED LEXICAL ITEM, LOAN WORD, ADOPTIVE, FOREIGN WORD, LEXICOGRAPHY, SOTHOIZED WORD, INDIGENOUS WORD, NATURAL SCIENCE, TECHNOLOGY, COMPOUND WORD, AMBIGUITYOpsomming: Natuurwetenskaplike en tegnologiese terminologie in die Sesotho sa Leboa eentalige woordeboek. Die hoofdoel van hierdie artikel is om 'n ver-gelykende ontleding te maak van die strukturele en die leksikale verskille tussen nuutskepping en transliterasie as metodes vir die verwerwing van vreemde natuurwetenskaplike en tegnologiese leksikale items wat bedoel is vir insluiting in die Sesotho sa Leboa omvattende eentalige woorde-boek PukuntÅ¡utlhaloÅ¡i ya Sesotho sa Leboa. Met die uitsondering van die meertalige woordelyste ("woordeboeke" soos hulle genoem word) wat deur die Nasionale Taaldiens van die Departement Kuns en Kultuur saamgestel word, het die Sesotho sa Leboa Nasionale Leksikografie-eenheid op die oomblik geen eentalige woordeboek wat spesialiseer in spesifieke onderwerpe soos die natuurwetenskap en tegnologie nie. As 'n begin het die Leksikografie-eenheid besluit om hierdie gespesialiseerde terminologie in die tweede uitgawe van sy omvattende eentalige woordeboek in te sluit. Die hoofdoel vir die lemmatisering van hierdie natuurwetenskaplike en tegnologiese terminologie is om hierdie leksikale items omvattende definisies in Sesotho sa Leboa te gee in plaas van " 'n eenwoordvertalingdefinisie" soos die geval is in die tweetalige en meertalige woordeboeke.Sleutelwoorde: TRANSLITERASIE, NUUTSKEPPING, NUUTGESKEPTE LEKSIKALE ITEM, LEENWOORD, ONTLENING, VREEMDE WOORD, LEKSIKOGRAFIE, VERSOTHODE WOORD, INHEEMSE WOORD, NATUURWETENSKAP, TEGNOLOGIE, SAMESTELLING, DUBBELSINNIGHEID